Stuttering: A Review for Counsellors and Teachers - Boberg, Einer; Calder, Peter (Canadian Journal of Counselling and Psychotherapy, 2012)
Theories concerning the onset of stuttering are grouped into three categories and briefly reviewed. Current treatment strategies are described. Guidelines for the counsellor and teacher are provided to enable them to work co-operatively with the speech pathologist toward more effective management of the stuttering child in the school setting.